2019
DOI: 10.1111/jen.12615
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive strategy as a major factor determining female body size and fertility of a gregarious parasitoid

Abstract: The generally known “adult size‐fitness hypothesis” (ASFH) is applied to the gregarious parasitic wasp Anaphes flavipes (Foerster, 1841) (Hymenoptera: Mymaridae). ASFH is dependent on the reproductive strategy of the mother, which means the larger females have more offspring compared to smaller females. Two main factors, the mother's body size and food quantity received during larval development, can affect the body size of the offspring. For the first time, we present a study on the relative effect of both fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 57 publications
1
46
0
Order By: Relevance
“…One ( a ), two ( b ) and three ( c ) wasps developing per host egg.
Figure 3The number of wasps developing in one host egg, their adult body size and future fertility are influenced by the host population density of the host. Each female has 34 offspring, but the size of their offspring depends on the number of individuals developed in one host 28 . Wasps lay a higher number of eggs into one host egg and therefore produce smaller offspring if the population density of hosts is “low” compared “medium” and “high” population densities of hosts.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One ( a ), two ( b ) and three ( c ) wasps developing per host egg.
Figure 3The number of wasps developing in one host egg, their adult body size and future fertility are influenced by the host population density of the host. Each female has 34 offspring, but the size of their offspring depends on the number of individuals developed in one host 28 . Wasps lay a higher number of eggs into one host egg and therefore produce smaller offspring if the population density of hosts is “low” compared “medium” and “high” population densities of hosts.
…”
Section: Resultsmentioning
confidence: 99%
“…The host spectrum of the wasp includes species of the genera Lema and Oulema (Coleoptera: Chrysomelidae), including an economically important crop pest - the cereal leaf beetle O. melanopus 25,27 . Recently, we observed that in comparison to smaller females, larger females have more offspring and that the adult size of the offspring is directly determined by the number of offspring developing in one host egg 28 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(O. duftschmidi Redtenbacher, 1874, O. gallaeciana Heyden, 1879, and O. melanopus Linnaeus, 1758) [22,23]. Larvae and adults of Oulema species damage the leaves of cereals (barley, wheat and oats), and they are an economically important crop pest in Europe and North America [24][25][26]. For example, in agricultural areas around the world, insect pests reduce grain crop yields by 5% to 20 % every year [27].…”
Section: Introductionmentioning
confidence: 99%